Answer: 7
Step-by-step explanation:
Step 1: Subtract 3 from both sides.
6a+3−3=45−3
6a=42
Step 2: Divide both sides by 6.
6a
/6
=
42
/6
We start out with x/3+6=-6. Subtract 6 from both sides, and you get x/3=-12. Multiply the equation by three and you get x=-36. x=-36 should be your final answer.
Answer:
L = 50 * (-0.4)^(n - 1)
Step-by-step explanation:
r = t2/t1 = -20/50 = - 0.4
a = 50
L = 50 * (r)^(n - 1) Let's see if we can get the answer when n = 3
L=50 * (-0.4)^(3 -1)
L =50* (-0.4)^2
L = 50 * 0.16
L = 8 which is correct